Analisis Persedian Bahan Baku, Reorder Point dan Safety Stock Bahan Baku ADC-12 - Hazimah Hazimah; Yongki Antoni Sukanto; Nurlinda Ayu Triwuri (Universitas Batanghari Jambi, 2020)
The production process is very dependent on the availability of raw materials. An optimal calculation of raw material inventory is needed so that the company avoids the problem of lack or over stock of raw materials. This research aims to find out the quantity of raw material inventory, safety stock, and reorder point for ADC-12 raw materials.. This research uses a quantitative descriptive approach. Data sources obtained directly from the company. Analysis of the data used using the Economic Order Quantity method. Based on research and calculation results that have been done, if the company uses the EOQ method the quantity of raw material inventory is 80,861 kg. The quantity of the safety stock is 2,768 kg with a reorder point (ROP) of 14,038 kg.